2003
DOI: 10.1159/000071694
|View full text |Cite
|
Sign up to set email alerts
|

Are Some Cases of Infected Pancreatic Necrosis Treatable without Intervention?

Abstract: Background: Infected pancreatic necrosis is considered an absolute indication for interventional management such as percutaneous drainage or surgery. The presence of retroperitoneal air is a sign of anaerobic sepsis. Method: A retrospective review of case records of patients presenting with severe acute pancreatitis and pancreatic necrosis was performed to identify cases in whom conservative treatment was followed by a satisfactory outcome. Results: Four patients were identified over a 3-year period who had pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…However, in the early 2000s, several studies showed percutaneous drainage was associated with decreased mortality when compared to open necrosectomy for acute necrotizing pancreatitis 31,32,33 . Subsequent investigations suggested that medical management alone without any procedural intervention could even be considered in certain cases of infected pancreatic necrosis 10,13,16,34,35 . Since then, there have been numerous publications supporting a conservative management strategy for infected pancreatic necrosis 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the early 2000s, several studies showed percutaneous drainage was associated with decreased mortality when compared to open necrosectomy for acute necrotizing pancreatitis 31,32,33 . Subsequent investigations suggested that medical management alone without any procedural intervention could even be considered in certain cases of infected pancreatic necrosis 10,13,16,34,35 . Since then, there have been numerous publications supporting a conservative management strategy for infected pancreatic necrosis 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…There are existing data to suggest that some patients with infected necrosis may not need intervention at all. [20][21][22] Patients with symptomatic WOPN are typically those who fail to progress clinically, have gastric outlet obstruction secondary to the necrosum, or have a deteriorating clinical condition despite maximal medical therapy without overt infection on Gram stain of the necrosum. Whether these patients would have improved without intervention remains a significant question; however, the clinical outcomes reported herein would suggest that DMD has a beneficial effect in such individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This has developed not from randomised data but observational studies over time that seemed to show a reduction in the previously reported mortality [3][4][5] . A small number of recent reports [6][7][8] have attempted to cast doubt on whether all patients with infected pancreatic necrosis should undergo surgery. So should a randomised controlled trial be undertaken?…”
mentioning
confidence: 99%